Strength does not correlate with speed in young futsal athletes - Dias, Karoline da Silva (2021)
Futsal is characterized as an intermittent sport modality involving aerobic and anaerobic activities. However, there is a predominance of the moderate and high intensity actions for being a dynamic modality requiring high physical demands, mainly strength and speed, from the athletes. Verify the correlation among the performances of vertical jumps with sprints and change of direction sprints in futsal players of the basic category under-15 and under-17. Materials and Methods: The sample was composed by 46 male gender players, being 19 of the under-15 category and 27 of the under-17 category. It was submitted to analysis, body composition and effort test to evaluation of vertical jumps (SJ and CMJ) and sprints (SL and COD). The normality of the data was verified by the Shapiro-Wilk test, for the correlations of the tests was utilized the correlation test of Pearson. For the analysis of the performances between the categories was utilized the non-paired t-test. The level of significance adopted was p < 0,05. Results: The values of correlation found for the under-15 category were r= -0,115 (SL and SJ), r= -0,007 (SL and CMJ), r= -0,141 (COD and SJ) e r= 0,131 (COD and CMJ). For the under-17 category it was found r= -0,243 (SL e SJ), r= -0,307 (SL e CMJ), r= -0,256 (COD e SJ) e r= -0,224 (COD e CMJ). The data from this study are similar to literature data that use the same sample and procedure characteristics. The correlation values were low and not significant showing that the vertical jumps and sprints have different demands and for this reason is necessary caution to use the VJ as a training method of speed, being necessary different trainings, considering the specificities of the tasks. Furthermore, the maturational stage must be considered for the progression of the loads of training and to obtain improvement in the performances.